2004
DOI: 10.1038/sj.bmt.1704633
|View full text |Cite
|
Sign up to set email alerts
|

Single agent dexamethasone for pre-stem cell transplant induction therapy for multiple myeloma

Abstract: Summary:Given the survival advantage, high-dose therapy (HDT) remains the standard of care for patients with multiple myeloma eligible for the procedure. For those undergoing HDT, initial therapy aimed at reducing tumor burden is given prior to stem cell harvest. Various regimens, mostly variations of VAD (vincristine, doxorubicin, dexamethasone), are used for induction therapy. We retrospectively evaluated if single agent dexamethasone would be an effective induction therapy, given that it is the most active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…Just 6% of patients showed disease progression. The CR rate compares favorably with the 0% CR/nCR rate reported with other single agents, including dexamethasone [63,64] and thalidomide [65], used to treat frontline myeloma. A preliminary timeto-event analysis has been completed for 34 of these 66 patients; the median duration of best response was 8.5 months, while the median TTP was 6 months.…”
Section: Single-agent Bortezomibsupporting
confidence: 53%
“…Just 6% of patients showed disease progression. The CR rate compares favorably with the 0% CR/nCR rate reported with other single agents, including dexamethasone [63,64] and thalidomide [65], used to treat frontline myeloma. A preliminary timeto-event analysis has been completed for 34 of these 66 patients; the median duration of best response was 8.5 months, while the median TTP was 6 months.…”
Section: Single-agent Bortezomibsupporting
confidence: 53%
“…59 Before the advent of IMiDs and bortezomib, single-agent dexamethasone (dex) and VAD (vincristine, Adriamycin (doxorubicin), dex) were the most commonly used approaches. [60][61][62] Several clinical trials were conducted in the past decade, first comparing these newer drugs in combination with dex against single-agent dex or VAD (Table 3). More recent trials have compared combinations of IMiDs and bortezomib together vs using them individually.…”
Section: Initial Therapymentioning
confidence: 99%
“…24 Treatment of patients with these regimens for 4-6 cycles typically resulted in response rates of 50-60% with only a small proportion of patients achieving a complete response prior to ASCT. [25][26][27] Previous studies have not demonstrated any long-term impact of the initial therapy on ASCT outcome in terms of TTP or survival, but these studies did not use novel agents in the induction phase. [6][7][8][9] The response status before the transplant had minimal impact on the eventual outcome of ASCT, with patients refractory to initial therapy obtaining as much benefit from the procedure as those who were responding to the pretransplant therapy.…”
Section: Discussionmentioning
confidence: 99%